Síntese de nanofios de Óxido de Cobre (CuO) e fabricação de nanodispositivos - Alem-mar Bernardes Goncalves (2008)
In this dissertation we are interested on the fabrication of electronic devices based on quasi one-dimensional nanostructures. To achieve such goal, we initially performed a study on the growth of copper oxide (CuO) nanowires with the intention of obtaining raw nanomaterial for preparation of the devices. CuO was chosen due to the simplicityof its growth process and because it has been little explored as nanostructure. We investigated nanowire synthesis using thermal oxidation, varying parameters such as time and temperature, with the objective to optimize and to understand the growth mechanism. From those studies, we discuss a growth model where the nanowires growdue to a driving-force generated by stresses that occur in the material during the oxidation process. Based on the experience acquired during the growth studies, a novel architecture for the manufacture of a interconnected arranje of nanowires was developed. Such architecture takes advantage of the fact that the nanowires grow perpendicular to the supporting Cu layer. Thus, by oxidizing two nearby Cu contact pads, the resulting CuO nanowires can bridge the contacts forming an array (or network) of sensing elements. We present results of the electrical characterization of devices based on this architecture for CO2 monitoring.We present here initial results on the fabrication of field effect transistors based on isolated CuO nanowires. Metal contacts were made by electron beam and optical lithography. We demonstrate that variations in the gate electric field result in changes in the conductivity of isolated nanowires. The observed dependence indicates that the nanowires behave as a p-type doped material. From such measurements, we could alsodetermine the nanowire carrier concentration and mobility.